Interventions towards barriers to the practice of physical activity in adolescence: A systematic review protocol - Terra, Lauryane Fonseca; Costa, Woska Pires da; Silva, Regina Márcia Ferreira; Rezende, Leonardo Mateus Teixeira de; Noll, Matias; Noll, Priscilla Rayanne E. Silva (PloS one, 2023)
Lack of regular physical activity is recognized as a global public health issue. Three out of every four adolescents do not adhere to physical activity recommendations. Thus, this systematic review will evaluate interventions employed to minimize barriers to physical activity among adolescents. Herein, we present the study protocol. To the best of our knowledge, this will be the first systematic review to assess the interventions implemented to minimize barriers to the practice of physical activity among adolescents. A systematic understanding of the most effective interventions to reduce the barriers to physical activity is essential. We will search five databases: two multidisciplinary (Scopus and Web of Science) and three other health-related databases (Embase, SPORTDiscus, and PubMed). The search will be limited to original peer-reviewed articles published in English, with no time restrictions. The search strategy will use MeSH terms and their variations to maximize the search strategy. Two reviewers will independently read the included articles, extract the data, and evaluate the methodological quality using the Grading of Recommendations, Assessment, Development, and Evaluation scale and the risk of bias using the Critical Appraisal Skills Programme checklist and Downs and Black scale. Discrepancies will be resolved by a third reviewer. This systematic review will follow the guidelines outlined in the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The outcomes of this study are expected to enhance the current understanding of the obstacles to physical activity among adolescents and aid in the development or modification of programs to combat physical inactivity in this population. Consequently, these findings should have a positive impact on current and future adolescent health outcomes. Ethical approval will not be required for this study as it is an analysis of previously published articles (i.e., secondary data). The results will be published in a peer-reviewed journal. PROSPERO registration: CRD42022382174.